Clinical Differences between Subtypes of Atrial Fibrillation and Flutter: Cross-Sectional Registry of 407 Patients - Almeida,Eduardo Dytz (2015)
Introduction:Atrial fibrillation and atrial flutter account for one third of hospitalizations due to arrhythmias, determining great social and economic impacts. In Brazil, data on hospital care of these patients is scarce.Objective:To investigate the arrhythmia subtype of atrial fibrillation and flutter patients in the emergency setting and compare the clinical profile, thromboembolic risk and anticoagulants use.Methods:Cross-sectional retrospective study, with data collection from medical records of every patient treated for atrial fibrillation and flutter in the emergency department of Instituto de Cardiologia do Rio Grande do Sul during the first trimester of 2012.Results:We included 407 patients (356 had atrial fibrillation and 51 had flutter). Patients with paroxysmal atrial fibrillation were in average 5 years younger than those with persistent atrial fibrillation. Compared to paroxysmal atrial fibrillation patients, those with persistent atrial fibrillation and flutter had larger atrial diameter (48.6 ± 7.2 vs. 47.2 ± 6.2 vs. 42.3 ± 6.4; p < 0.01) and lower left ventricular ejection fraction (66.8 ± 11 vs. 53.9 ± 17 vs. 57.4 ± 16; p < 0.01). The prevalence of stroke and heart failure was higher in persistent atrial fibrillation and flutter patients. Those with paroxysmal atrial fibrillation and flutter had higher prevalence of CHADS2 score of zero when compared to those with persistent atrial fibrillation (27.8% vs. 18% vs. 4.9%; p < 0.01). The prevalence of anticoagulation in patients with CHA2DS2-Vasc ≤ 2 was 40%.Conclusions:The population in our registry was similar in its comorbidities and demographic profile to those of North American and European registries. Despite the high thromboembolic risk, the use of anticoagulants was low, revealing difficulties for incorporating guideline recommendations. Public health strategies should be adopted in order to improve these rates.